Discovering the Bayou: successional restoration of Bayou Bienvenue - Kleinschmidt, Kristopher (Kansas State University, 2010)
All along the Gulf Coast, wetlands are disappearing due to saltwater intrusion from the draining of freshwater wetlands. Louisiana has about 40 percent of the coastal wetland in the lower 48 states but is currently losing approximately 24 square miles of wetlands a year (Louisiana Coastal 2009). Studies have shown that wetlands can help reduce the impact of a storm surge during a hurricane and have a cleansing ability from air to water. An increase in hurricane intensities due to climate change will likely result in bigger storm surges. Without wetlands to diffuse storm surges, disasters like Hurricane Katrina will recur. Cities spend millions of dollars on treating wastewater and stormwater with facilities and chemicals. Wetlands can treat wastewater through different processes without using chemicals, thus reducing costs and increasing sustainability. Bayou Bienvenue is a wetland located in New Orleans. This wetland was once a freshwater cypress swamp, but due to saltwater intrusion from the construction of Intracoastal Waterway and Mississippi River Gulf Outlet, has turned into a brackish lake. This wetland is separated from the Lower 9th Ward with a levee that creates a visual barrier which results in local residences not knowing that there is a former wetland behind the levee. Bayou Bienvenue’s Ecological Park’s discovery center with educational programs about successional wetland landscapes will educate people about the importance of wetlands to New Orleans. The restored of the bayou will be a landscape that functions as infrastructure through the treatment of stormwater and wastewater. The bayou will aid in reducing storm surge impacts, provide wildlife habitat, become part of schools’ curricula within the 9th Ward, stimulate the local economy and provide a community park for people to enjoy. Bayou Bienvenue’s Ecological Park will help spur further wetland projects of this caliber in and around New Orleans.
Keywords: Landscape Architecture; Restoration; Wetlands; Wastewater/Stormwater Treatment; Succession; Education; Landscape Architecture (0390)